2016
DOI: 10.1186/s13098-016-0188-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vitamin D status, glycemic control and cardiovascular risk factors in Brazilians with type 2 diabetes mellitus

Abstract: ObjectivesDetermine the prevalence and identify predictors of hypovitaminosis D in patients with type 2 diabetes mellitus (T2DM); 2) correlate vitamin D levels with variables indicative of glycemic control and cardiovascular risk.Research design and methodsWe conducted a cross-sectional study with consecutive patients treated at a University Hospital’s Endocrinology outpatient clinic located at 12°58′S latitude, between October 2012 and November 2013. Hypovitaminosis D was defined as 25-hydroxyvitamin D < 30 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
11
23
1
Order By: Relevance
“…In a study conducted by Brot et al it was observed that dietary vitamin D intake, non-smoking, and physical activity (in men) were significantly associated with higher concentrations of serum 25-hydroxyvitamin. 40 In a study conducted by Rolim et al total cholesterol (β=−0.36, p<0.01) and BMI (β=−0.21, p=0.04) was independently associated with levels of 25-hydroxyvitamin D. 41 Like earlier studies negative relationship was found between body mass index, systolic blood pressure, total cholesterol, age and vitamin D level in present study. However this relationship unlike earlier studies was not found to be significant.…”
Section: Resultssupporting
confidence: 68%
“…In a study conducted by Brot et al it was observed that dietary vitamin D intake, non-smoking, and physical activity (in men) were significantly associated with higher concentrations of serum 25-hydroxyvitamin. 40 In a study conducted by Rolim et al total cholesterol (β=−0.36, p<0.01) and BMI (β=−0.21, p=0.04) was independently associated with levels of 25-hydroxyvitamin D. 41 Like earlier studies negative relationship was found between body mass index, systolic blood pressure, total cholesterol, age and vitamin D level in present study. However this relationship unlike earlier studies was not found to be significant.…”
Section: Resultssupporting
confidence: 68%
“…In addition, the elevated intact parathyroid hormone (iPTH) observed in subjects with low 25(OH)D3 levels might play a causal role in the pathogenesis of increased adiposity (33). Similarly to our results, many studies have reported that patients with insufficient levels of vitamin D have high prevalence of dyslipidemia, they showed that the use of this vitamin might reduce levels of TG, TC, and might improve HDL-C level (34)(35)(36)(37). Vitamin D is shown to exert a role in the transportation of cholesterol by regulating the apolipoprotein A-1 levels, and it may act in the reduction of LDL-C uptake, may decrease the formation of foam cells, and may enhance the production of HDL-C.…”
Section: Discussionsupporting
confidence: 91%
“…A study of vitamin D supplementation in type 2 diabetics with coronary artery disease showed significant reduction in fasting plasma glucose, serum insulin, insulin resistance, and β cell function 15 . Hypovitaminosis D in diabetic patients was significantly correlated with the female gender, dyslipidemia and obesity 16 . Using multiple linear regression analysis, the total cholesterol and body mass index were defined as predictors for vitamin D insufficiency in Brazilian population 16 .…”
Section: Discussionmentioning
confidence: 93%
“…Hypovitaminosis D in diabetic patients was significantly correlated with the female gender, dyslipidemia and obesity 16 . Using multiple linear regression analysis, the total cholesterol and body mass index were defined as predictors for vitamin D insufficiency in Brazilian population 16 .…”
Section: Discussionmentioning
confidence: 93%